Effect of Medications on Physical Function and Cognition in Nursing Home Residents with Dementia. Issue 6 (13th May 2014) - Dutcher, Sarah K.; Rattinger, Gail B.; Langenberg, Patricia; Chhabra, Pankdeep T.; Liu, Xinggang; Rosenberg, Paul B.; Leoutsakos, Jeannie‐Marie; Simoni‐Wastila, Linda; Walker, Loreen D.; Franey, Christine S.; Zuckerman, Ilene H.
<x xml:space="preserve">Abstract</x> Objectives To assess the effectiveness of medications used in the management of Alzheimer's disease and related dementias (ADRD) on cognition and activity of daily living (ADL) trajectories and to determine whether sex modifies these effects. Design Two‐year (2007–2008) longitudinal study. Setting Medicare enrollment and claims data linked to the Minimum Dataset 2.0. Participants Older nursing home (NH) residents with newly diagnosed ADRD (n = 18, 950). Measurements Exposures included four medication classes: antidementia medications (ADMs), antipsychotics, antidepressants, and mood stabilizers. Outcomes included ADLs and cognition (Cognitive Performance Scale (CPS)). Marginal structural models were employed to account for time‐dependent confounding. Results The mean age was 83.6, and 76% of the sample was female. Baseline use of ADMs was 15%, antidepressants was 40%, antipsychotics was 13%, and mood stabilizers was 3%. Mean baseline ADL and CPS scores were 16.6 and 2.1, respectively. ADM use was not associated with change in ADLs over time but was associated with a slower CPS decline (slope difference: −0.09 points/year, 99% confidence interval (CI) = −0.14 to −0.03). Antidepressant use was associated with slower declines in ADL (slope difference: −0.36 points/year, 99% CI = −0.58 to −0.14) and CPS (slope difference: −0.12 points/year, 99% CI = −0.17 to −0.08). Sex modified the effect of both antipsychotic and mood stabilizer use on ADLs; female users declined most quickly. Antipsychotic use was associated with slower CPS decline (slope difference: −0.11 points/year, 99% CI = −0.17 to −0.06), whereas mood stabilizer use had no effect. Conclusion Despite the observed statistically significantly slower declines in cognition with ADMs, antidepressants, and antipsychotics and the slower ADL decline found with antidepressants, it is unlikely that these benefits are of clinical significance.